Association of vitamin E intake and malondialdehyde (MDA) levels with cognitive function in elderly residing at the Budi Mulia Tresna Werdha nursing home, East DKI Jakarta - Ria Angelia Putri; Novi Silvia Hardiany; Erfi Prafiantini (World Nutrition Journal, 2026)
Background: Cognitive dysfunction is one of the health problems associated with elderly. Oxidative stress is thought to play a role in the neurodegenerative process through increased production of free radicals that cause nerve cell damage. Vitamin E is an antioxidant that protects cell membranes from oxidative damage, whereas malondialdehyde (MDA) is a biomarker of oxidative stress produced by lipid peroxidation. The objective of this study is to analyze the association of vitamin E intake and MDA levels with cognitive function among elderly residents of Budi Mulia 1 Nursing Home in DKI Jakarta, Indonesia. Methods: This secondary study employed a cross-sectional design using data derived from a primary study investigating the association between zinc intake, superoxide dismutase activity, and cognitive function among elderly. A total of 85 participants met the inclusion and exclusion criteria. Vitamin E intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), plasma MDA levels were measured from stored plasma samples, and cognitive function was evaluated using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). Results: The median age of the participants was 69 years (range: 60–91 years). The median vitamin E intake, plasma MDA level, and cognitive function score were 3.7 mg/day (2.5–3.8), 2.85 nmol/mL (1.88–6.77), and 16 (1–30), respectively. No significant association was found between vitamin E intake and cognitive function (r = 0.027; p = 0.806), nor between plasma MDA levels and cognitive function (r = 0.096; p = 0.380). Conclusion: There was no significant association between vitamin E intake or plasma MDA levels and cognitive function among elderly.